Simplify the expression 3y(2y-7)-3(y-4) for y = -3

Question

Simplify the expression 3y(2y-7)-3(y-4) for y = -3

in progress 0
Skylar 1 month 2021-09-22T22:45:46+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-09-22T22:46:52+00:00

    Answer:

    ⇢ p (y) = 3y (2y – 7) -3 (y – 4)

    ⇢ p (-3) = 3 {-3) {2 (-3) -7} -3 (-3 – 4)

    ⇢ -9 (-6 – 7) -3 (-7)

    ⇢ -9 (-13) +21

    ⇢ 117 + 21

    ⇢ 138‬

    0
    2021-09-22T22:46:53+00:00

    Answer:

    p(y) = 3y(2y-7)-3(y-4)

    p(-3) = 3(-3)[2(-3)-7]-3(-3-4)

           = -9[-6 – 7]-3(-7)

           = -9[-13]+21

           = 117 + 21

           = 138‬

    Hope this helps you…………………….

    Plz mark me the brainliest

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )